Advancing circular economy models: The synergistic role of service design and blockchain technology in enhancing sustainability and consumer engagement - Vera Gerasimova (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2024)
This paper examines the transformative potential of integrating Service Design and Blockchain technology within Circular Economy models, aimed at enhancing sustainability and consumer engagement. Through the lens of two in-depth case studies-the Circular Electronics Platform and the Sustainable Food Supply Chain-we illustrate how these innovations can significantly improve transparency, efficiency, and participation in sustainable practices. The first case study investigates into the electronics industry, demonstrating a platform that uses Blockchain to manage the lifecycle of devices, thus promoting recycling and reuse. The second case study explores a Blockchain-based platform that enhances transparency in the food supply chain, empowering consumers with information to make sustainable choices. Our analysis reveals that the synergy between Blockchain technology and Service Design not only addresses environmental challenges but also fosters a deeper connection between consumers and sustainable practices. We discuss the broader implications of these findings, including the potential for scalability, the importance of consumer trust, and the need for interdisciplinary collaboration to further embed sustainability into the fabric of our economies. The paper concludes with recommendations for future research, emphasizing the exploration of standardized frameworks, the role of policy, and the integration of emerging technologies to advance Circular Economy goals. This study contributes to the growing body of literature on sustainable practices by highlighting innovative approaches to integrating technology and design in the pursuit of environmental sustainability.
Keywords: Q57; O33; L86; 330; Blockchain Technology; Circular Economy; Service Design; Sustainable Practices; Transparent Supply Chain